Structural insights into substrate and inhibitor binding sites in human indoleamine 2,3-dioxygenase 1 - Ariel Lewis-Ballester (Nature Portfolio, 2017)
Human indoleamine 2,3-dioxygenase 1 (hIDO1) is an immunotherapeutic target for cancer therapy. Here, the authors present the substrate-, inhibitor- and effector-bound hIDO1 crystal structures, which give insights into the mechanism and reveal a second small molecule binding site, which is of interest for drug design.